1990
DOI: 10.1111/j.1349-7006.1990.tb02663.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of HTLV‐I Sequence in Cord Blood Mononuclear Cells of Neonates Born to HTLV‐I Antigen/Antibody‐positive Mothers by Polymerase Chain Reaction

Abstract: We developed a polymerase chain reaction (PCR) method which has high sensitivity and simple technique in order to investigate the presence or absence of human T lymphotropic virus type I (HTLV‐I) provirus in cord blood mononuclear cells of neonates born to HTLV‐I carrier mothers. Out of 40, three subjects were found to contain the HTLV‐I provirus genome. These three subjects remained HTLV‐I sequence‐positive in follow‐up study. On the other hand, when examined by a conventional technique for detection of HTLV‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

1991
1991
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 15 publications
1
11
0
1
Order By: Relevance
“…In line with previous reports (Fujino et al, 1992;Saito et al, 1991;Satow et al, 1991), our data indicate the possibility that human placental trophoblast may become persistently infected with HTLV-I in vivo but that this infection is likely to be of a limited productivity. It remains to be elucidated to what extent local factors, namely a cytokine network typically restricted to the placental micro-environment (Mitchell et al, 1993), may play a part in modulation of virus expression in the infected placental cells and thereby regulate transplacental passage of HTLV-I.…”
Section: Short Communicationsupporting
confidence: 81%
See 1 more Smart Citation
“…In line with previous reports (Fujino et al, 1992;Saito et al, 1991;Satow et al, 1991), our data indicate the possibility that human placental trophoblast may become persistently infected with HTLV-I in vivo but that this infection is likely to be of a limited productivity. It remains to be elucidated to what extent local factors, namely a cytokine network typically restricted to the placental micro-environment (Mitchell et al, 1993), may play a part in modulation of virus expression in the infected placental cells and thereby regulate transplacental passage of HTLV-I.…”
Section: Short Communicationsupporting
confidence: 81%
“…Several previous reports, however, have suggested that HTLV-I may be acquired in utero. In these studies (Saito et al, 1991 ;Satow et al, 1991) virus-specific DNA and antigens were detected in cord-blood lymphocytes from the offsprings of HTLV-I carrier mothers. These data argue that the placenta might play a direct role in the infection of the fetus.…”
mentioning
confidence: 99%
“…Whether the HTLV-I-positive lymphocytes survive longer and establish HTLV-I infection in the children remains to be re-evaluated by other confirmatory methods, such as polymerase chain reaction (PCR) to detect HTLV-I proviral DNA in lymphocytes of the relevant children (Kwok et aZ., 1988). Indeed, Saito et al (1989Saito et al ( , 1990 reported several cases of HTLV-I-seronegative and PCR-positive children who were born to HTLV-I carrier mothers. On the other hand, Matsumoto et al (1990) reported a correlation between PCR positivity and IF seropositivity in HTLV-I-infected donors.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the study, about 10.5 to 39.6% of breast‐fed children born to HTLV‐I‐seropositive mothers become infected (Hino et al, 1996; Hirata et al, 1992; Nyambi et al, 1996; Takahashi et al, 1991; Tsuji et al, 1990; Wiktor et al, 1993, 1997; Yoshinaga et al, 1995) as compared with only 0 to 12.8% of bottle‐fed children (Hino et al, 1996; Hirata et al, 1992; Takahashi et al, 1991; Tsuji et al, 1990), suggesting that transplacental or other modes of transmission may also operate. An early study advanced this hypothesis, based on detection of HTLV‐I‐proviral DNA in cord‐blood samples, to explain the seroconversion of bottle‐fed children (Saito et al, 1990). But in a follow‐up study on bottle‐fed children, none of 7 children found HTLV‐I‐positive by PCR in their cord blood seroconverted, while 9 children who gave negative PCR results seroconverted (Hino et al, 1997; Kawase et al, 1992).…”
mentioning
confidence: 99%